Pengaruh Kompetensi dan Pengembangan Karir terhadap Kinerja Karyawan pada PT. Hadji Kalla Cabang Urip Sumohardjo Makassar dengan Employee Engagement sebagai variabel intervening - Tiong, Piter; Sumaryo, Partono; Dalle, Muhammad Yunus; Latif, Abdul (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2023)
The purpose of this study was to analyze and examine the effect of competency and career development on employee engagement and employee performance. Analyzing the effect of employee engagement on performance, as well as analyzing the effect of employee engagement in mediating the effect of competency and career development on employee performance at PT. Hadji Kalla, Urip Sumohardjo Makassar Branch. This research uses a quantitative approach by distributing questionnaires, with data analysis techniques using path analysis. The results of the study found that competency and career development have a direct effect on employee engagement and employee performance. Then employee engagement has a direct effect on employee performance. From the results of the sobel test, it can be concluded that employee engagement can mediate the influence of competency and career development on employee performance at PT. Hadji Kalla Urip Sumoharjo Branch.